Development of New Venture Support Networks and the Role of "Promoters" - Lambert T. Koch; Teemu Kautonen; Marc Gruenhagen (European Regional Science Association (ERSA), 2003)
New Venture Support Networks (NVSN) are a political instrument for the purpose of contributing to regional economic development by fostering more and qualitatively better start-ups. NVSN bundle together different available sources of information and consultation for potential entrepreneurs, including e.g. authorities, universities, financial institutions, trade associations and private consultants. Achieving effective cooperation between such a wide range of institutions is not a simple task. The initial situation is often characterised by conflicts between the varying individual interests of the participants and the politically defined goal of fostering more and better start-ups. Moreover, since the network has been established by a political initiative for a pre-determined funding period, the actor relations within it are “artificial” (as opposed to naturally developed). Thus, the actors lack common experiences, social bonds, values and other common motivators contributing to trust-based cooperative relationships. Such relationships are a crucial factor in turning the “artificial” network into a “real” one, which continues to exist also after the political funding period is over. Our hypothesis is that certain key actors are a critical success factor in developing NVSN into “real” networks. Following the “promoter model” – an expansion of champion models that has established itself in the German innovation management literature – we suggest that there are administrative, organisational and know-how related barriers that are detrimental to the development of NVSN. The overcoming of these barriers requires a combination of different organisational resources, which the promoter model discusses in terms of three different ideal types: promoter by power, promoter by know-how, and relationship promoter. One person can act in one or more of these roles simultaneously and the roles can appear in different combinations, known as promoter structures. The specific research objectives of the proposed paper are to identify a) the types of barriers faced in the different developmental stages of NVSN and b) the roles the key actors play and the resources they use in coping with them. Our sample consists of key actors in five regional NVSN in Germany, which were established in 1998 as part of the governmental initiative “EXIST – Entrepreneurs from Universities”. The author team is also involved in one of these networks. Using a grounded theory based qualitative approach, we intend to map the development process of these NVSN with respect to the above research objectives. The contribution of the study is two-fold: 1) It presents the first application of the promoter model in the context of NVSN and produces tentative results that can be used as a basis for further research. 2) It offers practical implications to NVSN by analysing how their effectiveness and continuity could be improved by an effective use of promoter structures.
Keywords: 330